Summary of Experience in Teaching Postgraduate Students majoring in Auditing to Learn Auditing Standard 1502 - Chen, Jin (International Journal of Global Economics and Management, 2024)
In order to make the audit report more transparent in reflecting the business status of the enterprise, better serve stakeholders, and align with international standards, China has continuously improved the audit report to meet market demand. The audit report introduces non unqualified opinion audit reports from four aspects: report type, report changes, report analysis, and impact, to help report adaptors understand this type of audit report. This article mainly summarizes the experience of teaching graduate students majoring in auditing to learn auditing standard 1502, in order to enable them to learn how to issue correct non unqualified audit reports and improve their professional literacy.